Extemporaneous Compounding and Stability Evaluation of Paracetamol-honey Based Syrup for Pediatric use - Zaid, Abdel Naser (Asian Journal of Pharmaceutics (AJP), 2016)
Background: Paracetamol is an analgesic and antipyretic agent. Honey is a nutrient that has many medicinal benefits and uses. It is has a demulcent activity and used in alternative medicine as a mild antitussive agent. Moreover, honey demonstrated an antitoxic activity in paracetamol-induced hepatotoxicity. Objective: The aim of this study is to formulate and assess the general stability of paracetamol-honey based syrup using four different sources of honey. Materials and Methods: Four different formulas of paracetamol-honey based syrup were prepared by changing the source of honey. The formulated syrups were then stored at two different storage conditions (25Â°C and 40Â°C). The organoleptic properties, microbial contamination, pH, and assay were assessed according to compendia guidelines. An ultraviolet spectrophotometer was used to quantify paracetamol in the obtained syrups. Results: Formula four (F4) honey-based syrup showed the best stability within 4-month period at both room and accelerated conditions. The pH remained constant, no change in organoleptic properties was observed, and the assay of paracetamol was always higher than 93% of the initial value. However, formula three (F3) of honey showed the worst stability. Conclusion: Honey would be a beneficial alternative for common syrup due to its numerous benefits in the medicinal field. Pharmacist and industry could benefit from F4 formulation to produce this kind of syrup to achieve an antitussive formulation with antipyretic activity and nutritional value.